2011
DOI: 10.1017/s1474746411000443
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Debt Advice as a Response to Financial Difficulties in Ireland

Abstract: Irish social policy has, since the early 1990s, prioritised debt advice as the primary policy tool for addressing over-indebtedness, targeting low-income households in particular. This article, which draws on secondary analysis of datasets and qualitative interviews, suggests that 'person-centred' debt advice plays a major role in alleviating personal overindebtedness and its effects among this group. However, the government's objective that it should facilitate financial independence is unrealistic. For such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Studies in the 1990s indicated that debt advice leads to short-term alleviation of financial pressures, but that over time debt problems resurface, especially in low income households as these struggle to maintain payment plans (Hinton and Berthoud, 1988; Mannion, 1992; Jones et al ., 1993; Money Advice Trust, 1999). Recent research underlines the positive short-term impact of debt advice (Muller et al ., 2012; Stamp, 2012) and, although evidence remains patchy, is more optimistic about the intermediate and longer-term effects, pointing to enduring positive effects not only on clients’ financial situation, but also on their health, wellbeing and outlook for the future (Balmer et al ., 2006; Pleasence et al ., 2007; Turley and White, 2007; Orton, 2010).…”
Section: Evidence On the Impact Of Financial Counsellingmentioning
confidence: 99%
“…Studies in the 1990s indicated that debt advice leads to short-term alleviation of financial pressures, but that over time debt problems resurface, especially in low income households as these struggle to maintain payment plans (Hinton and Berthoud, 1988; Mannion, 1992; Jones et al ., 1993; Money Advice Trust, 1999). Recent research underlines the positive short-term impact of debt advice (Muller et al ., 2012; Stamp, 2012) and, although evidence remains patchy, is more optimistic about the intermediate and longer-term effects, pointing to enduring positive effects not only on clients’ financial situation, but also on their health, wellbeing and outlook for the future (Balmer et al ., 2006; Pleasence et al ., 2007; Turley and White, 2007; Orton, 2010).…”
Section: Evidence On the Impact Of Financial Counsellingmentioning
confidence: 99%
“…No. 2, September 2018: 89-101 EISSN : 2442-9813 ISSN : 1829 England, 2010; Stamp, 2011;Bunn, 2014;Rickard Straus, 2015). Pengaruh media visual, online, iklan dan internet Wu, 2006, 2008;Smith, et al, 2008;Cynamon and Fazzari, 2008;Rutherford and DeVaney, 2009;Legge and Heynes, 2009;Carradore, 2012;Ashraf, et al, 2013;Kennedy, 2013;Kamil, et al, 2014;Alam, et al, 2014).…”
Section: Hasil Dan Pembahasanmentioning
confidence: 99%
“…Low-income and/or indebted households often rely on government funded schemes, such as the UK Citizens Advice Bureau (CAB) or Money Advice and Budgeting Service (MABS) in Ireland, for impartial advice and support to alleviate their financial situation through, for example, negotiating manageable repayment terms (Stamp, 2012). Stamp's (2012) recent research on MABS in Ireland shows how important money advice can be to help develop financial capability and financial inclusion, particularly in households with limited financial resources and financial security. Moreover, in seeking financial advice, many respondents reported increased wellbeing and quality of life (Stamp, 2012).…”
Section: Household Money Managementmentioning
confidence: 99%
“…However, in the current financial climate these face-to-face services are at risk of closure in the UK despite a short-term reprieve from government funding cuts (Stratton, 2011). This is perhaps because, as a result of the financial crisis, the definition of over-indebtedness has become more nuanced and is ‘a situation that can affect anybody, not just those on a low-income’ (Stamp, 2012: 23). The financial crisis has therefore stimulated debate around the management of household assets and debts and the need for greater individual financial capability.…”
Section: Household Money Managementmentioning
confidence: 99%
See 1 more Smart Citation